Usefulness of Elevated Troponin to Predict Severity in Patients with COVID-19 - Nowaz, Kazi Alam; Haque, AFM Shamsul; Sultana, Syeda Aleya; Malek, Mohammad Abdul; Rahman, Waliur; Kamal, Mostafa; Haque, Md Sanaul; Farjana, Jinat; Khondaker, Md Noornabi (University Heart Journal, 2022)
Background: Coronavirus disease 2019 (COVID-19) has produced a significant health burden worldwide. Recent studies had shown that cardiac injury in COVID-19 is not uncommon and may leads to death. The aim of this study was to assess cardiac troponin in patients with COVID-19 and to evaluate the incidence of myocardial injury. Methods: A cross-sectional study was designed among 100 hospitalized patients with moderate to severe COVID-19 in Combined Military Hospital (CMH), Dhaka from January to April, 2021, after considering inclusion and exclusion criteria, study population was divided into two groups on the basis of normal and elevated troponin level. Results: Participants had mean age of 67.33 ± 7.63 years with 76% men. 42% population had elevation in troponin levels. Risk factors like age, Diabetes (DM), C-reactive protein (CRP), Lactate dehydrogenase (LDH), D- Dimer, Ferrtin level were more in elevated troponin group and statistically significant. Troponin levels significantly increased with increasing severity of COVID-19 staging (Kendall’s tau-b =0.479, p= 0.004) with reflected moderate positive correlation. Multivariate analysis was performed for association of COVID- 19 severity with elevated troponin separately after adjusting for other known confounding factors. Independent association between COVID-19 severity and troponin remained significant after that along with other acute phase reactants and inflammatory markers. Conclusion: COVID-19 can significantly leads to myocardial injury. This data suggested elevated troponin level is one of the determinants of clinical outcome in patients with COVID-19. University Heart Journal 2022; 18(1): 29-35